Impact of Subgoal Labeling on Online Worked Example Learning in Mathematics for Primary School Students - Guan, Xiao; Du, Xuejiao; Lin, Hongxin (Frontiers in Education, 2022)
The no-subgoal-worked examples and the subgoal-worked examples are “one problem and two solutions.” Previous studies have found that the effect of subgoal-worked examples learning is better than that of no-subgoal-worked examples. However, there is still ambiguity around the subgoal-worked examples learning effect and mechanism of the subgoal labeling form. To address this issue, the current study recruited a total of 130 Chinese children (Mage = 8.78 years) to mathematical online learning under different worked example forms. The results revealed that, as compared with the no-subgoal-worked example, the subgoal-worked example increased primary school students’ working memory resource depletion. However, it did not improve their scores. Moreover, as compared with the subgoal-worked example, the focused subgoal-labeled worked example did not promote primary school students’ learning effectiveness in mathematics. However, the individual choice subgoal-labeled worked example improved primary school students’ near-transfer scores. It also reduced their mental effort and working memory resource depletion. It, therefore, appears to be a more effective subgoal-labeled worked example learning approach.